Respuesta :
1.
A quadratic equation has the general formula
expressed as:
ax^2 + bx - c = 0
This equation can be solved by the quadratic formula which is expressed as:
x = ( -b (+ or -) √(b^2 - 4ac) / 2a
From the given equation,
a = 8
b = 16
c = 3
x = ( -16 (+ or -) √(16^2 - 4(8)(3)) / 2(8)
x1 = -0.21
x2 = -1.79
Answer:
Step-by-step explanation:
Given that Patel is solving the quadratic equation
[tex]8x^2 + 16x + 3 = 0[/tex]
This can be done by factorisation or using formula or completion of squares method.
Since factorization does not seem to be possible let us resort to completion of squares method.
[tex]8x^2 + 16x + 3 = 0\\8(x^2+2x)+3=0\\8(x^2+2x+1-1)+3 =0\\8(x+1)^2-8+3=0\\(x+1)^2 =\frac{5}{8} \\x=-1+\sqrt{ \frac{5}{8}}\\x=-1-\sqrt{ \frac{5}{8}[/tex]